2017
DOI: 10.1007/s00277-017-3076-9
|View full text |Cite
|
Sign up to set email alerts
|

GATA2 gene analysis in several forms of hematological malignancies including familial aggregations

Abstract: The genetic predisposition to familial hematological malignancies has been previously reported highlighting inherited gene mutations. Several genes have been reported but genetic basis remains not well defined. In this study, we extended our investigation to a potential candidate GATA2 gene which was analyzed by direct sequencing in 119 cases including familial aggregations with a variety of hematological malignancies and sporadic acute leukemia belonging to Tunisian and French populations. We reported a delet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Increasing evidence has shown that GATA2 expression is correlated with hematologic pathophysiologies and the proliferation and progression of solid tumors [40]. Upregulated GATA2 expression has been implicated in several tumour types, such as breast cancer [41], colorectal cancer [42] and liver cancer [43]. Moreover, recent studies confirmed that GATA2 overexpression in prostate cancer increases cellular motility and invasiveness, proliferation, tumorigenicity, and resistance to standard therapies [40].…”
Section: Discussionmentioning
confidence: 98%
“…Increasing evidence has shown that GATA2 expression is correlated with hematologic pathophysiologies and the proliferation and progression of solid tumors [40]. Upregulated GATA2 expression has been implicated in several tumour types, such as breast cancer [41], colorectal cancer [42] and liver cancer [43]. Moreover, recent studies confirmed that GATA2 overexpression in prostate cancer increases cellular motility and invasiveness, proliferation, tumorigenicity, and resistance to standard therapies [40].…”
Section: Discussionmentioning
confidence: 98%
“…Neither the case described by us nor those presented by other investigators explains the relationship between GATA2 haploinsufficiency and the development of lymphoblastic neoplasms. Several authors have attempted to find a deleterious GATA2 mutation in familial and sporadic cases of lymphoblastic tumors (3,16). Collin et al suggested that the GATA2 transcription factor plays not only an important role in early hematopoiesis, but it can also affect B cell differentiation (17).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has shown that GATA2 expression is correlated with hematologic pathophysiologies and the proliferation and progression of solid tumors [40]. Upregulated GATA2 expression has been implicated in several tumour types, such as breast cancer [41], colorectal cancer [42] and liver cancer [43]. Moreover, recent studies con rmed that GATA2 overexpression in prostate cancer increases cellular motility and invasiveness, proliferation, tumorigenicity, and resistance to standard therapies [40].…”
Section: Discussionmentioning
confidence: 99%